Peer Critiquing in Scientific Inquiry: Enhancing Preservice Teachers' Reasoning, Epistemic Knowledge, and Scientific Argumentation through Innovative Teaching Strategies in an Undergraduate Science Content Course - Esther Kataate Namakula; Valarie L. Akerson (Journal of Education in Science, Environment and Health)
The study explored the impact of peer critiquing on preservice teachers' understanding of the nature of science, scientific inquiry, and argumentation in an undergraduate science content course. The aim was to investigate innovative teaching strategies that enhance preservice teachers' comprehension of these key aspects. This study showcased implementing these strategies in which the preservice teachers actively critique and evaluate each other's work, fostering a culture of constructive feedback and reflection. Data were collected from 38 preservice teachers from three data sources that included a group argumentation of an assigned environment scenario of the endangered species, a peer critique of a video presentation of the scientific explanation of an individual environmental science topic, and finally a peer critique on someone else’s scientific inquiry study that could either be observational or experimental. To achieve this goal, we used the class activities to incorporate new ideas within the classroom by documenting the preservice teachers’ practices as they reflect upon their peers’ practices.  While video critiques indicated a general competency, there was a need for further development in analyzing scientific concepts. The final class critiquing session demonstrated preservice teachers' self-awareness and understanding of the importance of relevant research in scientific inquiry. Peer critiquing activities positively impacted preservice teachers' reasoning skills, as evidenced by their ability to construct well-reasoned arguments and analyze empirical evidence. By examining preservice teachers' experiences and outcomes, we seek to provide valuable insights and recommendations for educators striving to enhance preservice teachers' understanding of the nature of science and scientific inquiry through peer critiquing.